PENGOLAHAN LIMBAH KULIT KOPI (Coffea sp) SECARA SEDERHANA UNTUK MENGGANTIKAN SEBAGIAN JAGUNG DAN PENGARUHNYA TERHADAP KUALITAS KARKAS AYAM PEDAGING - Garing, Yunita; Poli, Z.; Nangoy, F.J.; Montong, P.R.R.I. (Universitas Sam Ratulangi, 2020)
CARCASS QUALITY OF BROILER FED RATION CONTAINING COFFEE (Coffea sp) HUSK WASTE PRODUCT TREATED BY SIMPLE PROCESSING AND SUBSTITUTING PARTS OF CORN WITH DIFFERENT LEVELS. The aim of this research was to know coffee husk waste product treated by simple processing and substituting parts of corn on body weight, carcass percentage and weight of abdominal fat Study was applied at Faculty of Animal Science, Sam Ratulangi University during 35 days. Total of 144 day old chick unsexed broilers, strain of CP 707, involving 36 experimental units of battery pens were used in this study. Each unit of pen was filled 4 birds under completely randomized design on factorial patter of 3x4. Factor A was focused on three processing treatments including coffee husk heated under sun light (A1), coffee husk immersed in the water (A2), and coffee husk boiled under water (A3). Factor B was focused on four treatments of substitution levels including ration containing corn without coffee husk substitution (B0), ration containing corn substituted with 25% coffee husk (B1), ration containing corn substituted with 50% coffee husk (B2), ration containing corn substituted with 75% coffee husk (B3). Variables observed were including final body weight, carcass weight percentage and abdominal fat weight. Analysis of variance showed that interaction of processing treatments did not affect significantly on final body weight, carcass weight percentage and abdominal fat weight. This study showed that utilization of coffee husk waste product by above simple processing could substitute part of corn in ration of 25% - 75% producing high carcass quality of broiler. Key word: Coffee husk by product, corn, broiler carcass percentage